Telemedicine and Healthcare (International Journal of Medical and Allied Health Sciences, 2025)
In India as well as around the world, telemedicine has paved the way for new developments in the medical field. The majority of physicians and administrators in India are still unsure about the medicolegal implications of telemedicine practice. It is regarded as the practice of treating patients via telecommunication, hence offering significant healthcare to areas with limited incomes. It is the process of disseminating several facets of health information via a virtual platform powered by technology. The goal of telemedicine is to provide more access to high-quality medical care.